The Vital Function of Motivation and Attitude in Learning English as a Foreign language in the Moroccan University - Rym Asserraji; Aahd Asserraji; Yussef Aboudi; Handoko Handoko (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
Most academic researchers argued that learning English necessitates a number of components to effectively enhance the learning process. The major components that are highly demanding are mainly motivation and attitude. This study aims to check upon the significant role of the previously mentioned components in learning English as a foreign language and to check whether motivation and attitude are highly required for an efficient learning process. For the data collection procedure, a google form questionnaire was designed and distributed to respondents through the social media applications, such as WhatsApp, Facebook and Messenger too. The respondents of this study are Moroccan university students affiliated to Moulay Ismail University in Meknes in Morocco, more precisely the Faculty of Letters and Human Sciences as well as the Faculty of Sciences in Meknes in Morocco. For the research outcomes of the study, respondents were aware about the requirement of enhancing their level in English. They held an encouraging attitude towards the language. They illustrated that they have become tolerant and open-minded in their process of learning. They also assumed that English is a global language and they are studying it for various reasons, such as passing exams successfully, delivering talks and publishing articles in internationally indexed journals, and settling in a foreign country whose English is the mother tongue of its native speakers. Consequently, they are adopting intrinsic/extrinsic and instrumental/integrative motivation clusters. Likewise, they argued that they ought to practice the language inside and outside the classroom setting to become fluent in English; otherwise, it will be hard for them to achieve an excellent level in the learning process. At last, it can be deduced that students’ motivation and positive attitude are tremendously relevant for an effective learning process of a foreign language.